Estudo da produção e divulgação científica do Instituto Federal de Educação, Ciência e Tecnologia de São Paulo - Santos, Marcel Pereira (Universidade Federal de São Carlos, 2014)
The Federal Institutions of Education, Science and Technology were created on December 23rd 1909 through the decree number 7.566 and named Escolas de Aprendizes Artífices ( Schools of craftsmen apprentices ). Those schools initially aimed at providing primary, vocational and free education. In 1959, they became the Escolas Técnicas Federais ( Federal Technical Schools ). On January 18th 1999, a decree without number transformed them into the Centros Federais de Educação Tecnológica - CEFETs ( Federal Centers of Technological Education . In 2008, through the sanction of law number 11.892, the CEFETs became the Institutos Federais de Educação, Ciência e Tecnologia ( Federal Institutes of Education, Science, and Technology ). With this last transition, the Federal Institutes acquired a University status and priviledged the triangulation Teaching, Research, and Extension . Currently, some difficulties to research can be easily found within those institutes, as well as issues to localize and mainly centralize that triangulation so as to use them as guides and contributors to scientific and technological development of the IFSP. The aim of this work is to provide an analytical survey of the scientific production of the IFSP and highlight which practices related to the dissemination of scientific knowledge are in fact carried out at the IFSP. This research was theorical and exploratoty and carried out based on a bibliographical survey linked to its field. A mapping of the scientific production done by IFSP professors who work in higher education was traced through bibliometrics in order to provide the indicators. These, in turn, were determined by the collection of data through the software scriptLattes, the one that registers all the scientific production of Lattes curriculums available at the online Lattes platform. A questionnaire was used as a tool to acquire information about the professors, as well as to frame IFSP researchers's profiles. The results were achieved through the following: the mapping of scientific production indicators carried out by IFSP professors who work in higher education; a surveying of the actions related to the dissemination of scientific knowledge; the professors's perspectives related to researching and the dissemination of institutional scientific knowlegde. In conclusion, the transformation of the old CEFET-SP into the current IFSP has yet to impact in development of institutional research. However incipient, research is indeed carried out at the IFSP, even though the dissemination of scientific knowledge is practically inexistent. Is it worth pointing out that the time it took for this transformation to happen was quite short for a centenarian institution like the IFSP. A longer period is in fact needed for the modifications to be identified. This study is concluded with some suggestions aimed at providing improvements concerning both institutional research and the dissemination of scientific knowledge.
Keywords: Desenvolvimento da ciência e tecnologia; Produção científica; Indicadores de desempenho; Bibliometria; Instituto federal; Divulgação Científica; Federal institute; Scientific production; Indicators; Bibliometrics; Dissemination of scientific knowledge; CIENCIAS SOCIAIS APLICADAS